PENGARUH KOMITMEN ORGANISASI DAN PENERAPAN KEBIJAKAN AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PADA PEMERINTAH DAERAH KABUPATEN ACEH BESAR - Tengku Rayya Aqila; Fifi Yusmita (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study examines the effect of organizational commitment and the application of accounting policies on the quality of financial reports in the Aceh Besar District Government. The type of this study is quantitative descriptive research. The sources of data in this study are primary data obtained through the distribution of questionnaires and interviews. The population in this study is all Local Government Work Units (SKPD) in the Aceh Besar District represented by Financial Administration Officers, Head of Sub Division of Finance, Finance Section Staff, and Treasurer, with a total of 116 respondents out of 58 Local Government Work Units. The sampling technique in this study used saturated sampling, where the entire population was used as the research sample. The data analysis method used is multiple linear regression using the SPSS Version 26 application. The results show that (1) organizational commitment and the application of accounting policies have a joint effect on the quality of financial reports; (2) organizational commitment affects the quality of financial reports; and (3) the application of accounting policies affects the quality of financial reports. The results of this study are expected to provide suggestions for the Aceh Besar District Government in policy making, especially those related to organizational commitment and the application of accounting policies, so as to further improve the quality of financial reports.